Operative Treatment for Advanced Colorectal Cancer in RSKD - -, Ajoedi; Kastomo, Dukut (Indonesian Journal of Cancer, 2008)
Operative Treatment for Advanced Colorectal Cancer in RSKDÂ full text: http://www.scribd.com/doc/45153087/Operative-Treatment-for-Advanced-Colorectal-Cancer-in-RSKD